Mandatory Rules of Public Policy Concerning Consumer Protection in Recent Jurisprudence - Ana Juanita GOICOVICI (Transylvanian Review of Administrative Sciences, 2013)
The following article attempts to dismantle the assumptions that the administrative acts oriented towards consumer protection can be subsumed under the unitary concept of ‘public policy’, in the context in which the contemporary administrative and legislative measures tend to be divided into two categories: (a) those related to the State’s economic intervention (public policy of direction) and (b) those pertaining to the protective and anticipatory legal intervention (public policy of protection). The fundamental issue that needs to be addressed is whether it is possible to refine the concept of ‘mandatory rules of public policy’, despite its appearance as a vague notion, giving it a precise, positive and unequivocal meaning. Since the interests at stake are general and reverberating on national economy, the mandatory character of the rules pertaining to the public policy of direction is absolute, as none of the protagonists (consumer or professional) is allowed to deviate from the rules involved. Thus the infringement of a mandatory rule from this category protects the interests of the society as a whole, while the interests usually attached to the rules of public policy of protection are fundamentally individual, though common to large groups of consumers who may find themselves placed in a similar situation.